Consistency and Utility of Data Items Across European Rheumatoid Arthritis Clinical Cohorts and Registers. Issue 9 (26th August 2015) - Radner, Helga; Dixon, William; Hyrich, Kimme; Askling, Johan
Abstract : Objective: To identify overlaps, discrepancies, and perceived utility of the currently collected data in European clinical rheumatoid arthritis (RA) cohorts and registers. Heterogeneity of data collection and data representation may limit comparative and collaborative RA research. Defining data standards is important and should be informed by which data items are currently collected and their perceived utility in scientific analyses. Methods: A web survey was sent to 27 European RA registers/clinical cohorts, requesting information on which specific data items were collected, how and with what frequency they were collected, how often data were missing, and if the items collected were regarded as useful for research. Results: Twenty‐five of 27 contacted RA cohorts/registers from 16 different European countries, totaling 189, 633 patients (range 130–55, 000), completed the survey. Items collected by the majority of data sources and used frequently for research were composite disease activity scores, acute‐phase reactants, joint counts, information on RA‐specific treatments, physical function, and patient global assessment of disease activity. Many of the collected items showed large variability in terms of measurement and time point of collection. Among all items collected, disease activity, RA treatment, and joint counts were regarded as the most important. When not collected, smoking, imaging, and comorbidities were the top‐ranked variables felt to have been worth collecting. Conclusion: Even though certain items are regularly collected, the mode of data collection and the data definition are heterogeneous. Harmonization of data collection across European clinical RA data sources is therefore pivotal for future collaborative studies.